1960
DOI: 10.1084/jem.112.5.945
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Two Kinds of Virus Particles Which Comprise Influenza A2 Virus Strains

Abstract: Seven strains of influenza A2 virus were serially passed in the chick embryo, and morphological characteristics of the passages were examined in the electron microscope. With serial passage there was a change from a prominently filamentous appearance in early passages to an almost entirely spherical appearance in later passages. The number of passages required for the conversion to spherical morphology varied with different strains. The filament-sphere variation was found to be independent of the properties wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…The ability to form filaments and spheres is similar to the observation that influenza virus forms both types of particles, depending on culture conditions and cellular or viral factors (3,6,10,24,27,31,40,41,44). Thus, there is support for the idea that mixed morphogenetic populations of particles can be formed from identical viral structural components.…”
Section: Discussionsupporting
confidence: 67%
“…The ability to form filaments and spheres is similar to the observation that influenza virus forms both types of particles, depending on culture conditions and cellular or viral factors (3,6,10,24,27,31,40,41,44). Thus, there is support for the idea that mixed morphogenetic populations of particles can be formed from identical viral structural components.…”
Section: Discussionsupporting
confidence: 67%
“…Our finding that the footprint of the regions on native HA trimers that interact with C179 closely matches the footprints identified by X-ray crystallography for the binding of other stem region antibodies suggests a conserved strategy of different stem antibodies to access this region of HA on native virions. The demonstration of similar structures of the complex on spherical and filamentous virions suggests that stem region antibodies elicited using spherical vaccine platforms (e.g., virus-like particles) are able to target stem regions on filamentous influenza forms that have been observed in influenza isolates for almost 70 years (35)(36)(37). An important conclusion that can be drawn from our structural analysis results is that the majority of virion-bound HA is accessible to a broadly neutralizing anti-stem antibody.…”
Section: Discussionmentioning
confidence: 53%
“…2A to H and Q). This result was surprising, as previous studies have reported conversion to a predominantly spherical morphology in some strains in 10 passages or fewer (9).…”
Section: Human Clinical Influenza Virus Isolates Produce Filamentous mentioning
confidence: 55%
“…Early studies revealed that filamentous strains gradually become spherical following repeated passage in embryonated chicken eggs (ECEs) (8,9). Whether this conversion also occurs upon passage in MDCK cells is unclear, as we were unable to find data on this point reported in the literature.…”
mentioning
confidence: 84%